Microstructural investigations of materials for low temperature co-fired ceramic (LTCC) based fuel cell using small angle neutron scattering - Mohamed A.A.; Ahmad M.H.; Ibrahim A.; Azman A.; Alias R.; Ambak Z.; Shapee S.; Putra E.G.; Patriati A.; Sharom M.A.; Yazid H.; Mamat M.R.; et al. (Institute of Physics Publishing, 2023)
The concept and the realization fuel cell based on LTCC technology require the investigations of fired LTCC microstructures. The majority of the works involved using small angle neutron scattering studies on the microstructural of LTCC ceramic tape and development of neutron tomography for future tool to visualize channels inside the fired tape. Most SANS characterization were carried out at Smarter SANS instrument at BATAN, Indonesia. Standard sample for resolving tens of micron of object size were measured using simple neutron tomography setup utilizing monochromatic SANS beam at Malaysian Nuclear Agency. The initial microstructural findings indicates that organic additives shape the final microstructural of LTCC after firing with the glassy material possibly fill the space left by the burned organic additives. The tomography results showed that 40 micron size object can be differentiated. The conductor deposited on LTCC is preliminary investigated which will later be used as support for catalyst. Published under licence by IOP Publishing Ltd.